THE GEODETIC MONITORING OF DEFORMATIONS OF A HIGH-RISE BUILDING USING GROUND-BASED LASER SCANNING TECHNOLOGY - Madimarova, Gulmira; Suleimenova, Diana; Pentayev, Toleubek; Khalykov , Yerkebulan; Baydauletova, Gulban; Tumazhanova, Saltanat; Stankova, Hana (Journal of Applied Engineering Science, 2022)
The article justifies the use of laser-scanning systems for geodetic monitoring of high-rise buildings and structures. Contemporary methods allow solving comprehensively the main tasks of geodetic monitoring. During the monitoring of high-rise objects, not only the main geometric parameters of the objects should be taken into account. The main importance should be given to the mutual arrangement of individual building elements, which is especially important for identifying and predicting deformation processes. Laser scanning coordinate measuring systems are designed to measure the object coordinate points to determine the object’s geometric dimensions. The principle of GLS operation is to measure the point coordinates in space by the polar method. Distance is measured by a laser rangefinder using a pulse method with signal digitization technology. The advantage of this approach is a smaller amount of time spent on the creation of a primary survey network. At that, the laying of scanner ray paths is most effective when carrying out ground-based laser scanning of linear structures. But it is advisable to apply its construction elements within the framework of the developed methodology. The development and implementation of new technologies for geodetic work performance, supported by an appropriate level of automation, is always carried out to reduce the time required for data collection and processing. The RiSCAN PRO program is a project-oriented product, i.e. the entire volume of data obtained as a part of a single measurement project is structured and stored according to the RiSCAN PRO project structure.
Keywords: monitoring, control point, deformation, stability, laser scanning